Gambaran Tingkat Pengetahuan Ibu tentang Toilet Training pada Anak Usia Toddler di Asrama Praja Raksaka Kepaon Denpasar - Bayu Asmara Putra Dewa; Ni Luh Made Asri Dewi; I Kadek Artawan (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Children are the greatest family asset, where in their growth and development stages children need proper nutrition, stimulation, and parenting so that they are in their golden age or golden age (0-5 years). Based on the National Household Health Survey (SKRT), there are 75 million children under five who have difficulty controlling BAK and defecating (bedwetting) until preschool age. Toilet training is best done from an early age to instill good habits in children. This study aims to determine the level of maternal knowledge about toilet training for toddlers at the Kepaon Denpasar Praja Praja hostel. Methods: This study uses descriptive research methods. The research was carried out in the Denpasar Kepaon Raksaka Praja Dormitory, with a total sample of 44 mothers. The sampling technique used in this study was total sampling. The method of data collection is by distributing questionnaire sheets. The data were processed using the Excel Microsof computer program and SPSS. Results: The results of the research of 44 respondents, namely the level of knowledge of mothers about toilet training for toddlers, all of them had a sufficient level of knowledge as much as 32 (72.7%), as many as 6 respondents (13.6%) had a good level of knowledge, and as many as 6 respondents (13.6%) have a low level of knowledge. Conclusion: It can be concluded that the level of mother's knowledge about toilet training for toddlers in the Denpasar Kepaon Praja Raksaka hostel is in the sufficient category.